Trade policy and national identity: Why Keynes was opposed to protectionist policies? - Elise S. Brezis (Bar-Ilan University, Department of Economics, 2020)
The views of Keynes on Trade policy are clear: Protectionism as well as hoarding a surplus in the balance of payment are wrong. This paper analyzes the optimality of protectionist policies and having a surplus in the context of the international political system. I show that in the situation of a hegemonic country, all classes - the working class as well as the elite - opt for free trade. But, in a balance of power context, wherein no single actor on the international scene possesses hegemonic status, the working class will choose protectionism, having a surplus, asking for harsh reparations, while the transnational elite and Keynes will not.
Keywords: B17; B27; E12; F30; 330; Balance of Power; Carthaginian Peace; Hegemony; Reparations; National Sovereignty; Trade Policy